Resolving gas-phase metallicity gradients of 0.1 ≲ z ≲ 0.8 galaxies. Issue Volume 14:Issue A30(2018) (August 2018) - Carton, David
Abstract: We present gas-phase metallicity gradients of 84 star-forming galaxies between 0.08 < z < 0.84. Using the galaxies with reliably determined metallicity gradients, we measure the median metallicity gradient to be negative ( \[ - 0.039_ - 0.009^ + 0.0071pt dex/kpc\] ). Underlying this, however, is significant scatter: (8 ± 3)% [7] of galaxies have significantly positive metallicity gradients, (38 ± 5)% [32] have significantly negative gradients, (31 ± 5)% [26] have gradients consistent with being flat. (The remaining (23 ± 5)% [19] have unreliable gradient estimates.)